INDEKS MASSA TUBUH (IMT) DENGAN KEJADIAN MENARCHE DINI - Aldita Mellyani, Retno; Puspita, Dinarwulan; Pradika, Jaka (Literasi Intelektual, 2024)
Background: The age of menarche in young women varies from year to year. One factor is nutritional imbalance, which can be assessed using the Body Mass Index (BMI). Objective: To find out whether there is a relationship between BMI (Body Mass Index) and the incidence of early menarche in Muhammadiyah 2 elementary school students, Pontianak city. Methods: This type of research uses analytic descriptive method with a cross sectional approach. The sample used was 78 respondents with the consecutive sampling method. Statistical test using the Chi-Square test. Results: Through analysis with the Chi-Square test obtained a significant level of α = 0.05. Based on the results of data processing, a sig (2-tailed) value of 0.002 <0.05 means that Ho is rejected, Ha is accepted, indicating that there is a relationship between body mass index (BMI) and the incidence of early menarche in elementary school students at Muhammadiyah 2 Pontianak. Conclusion: There is a relationship between body mass index (BMI) and the incidence of early menarche in Muhammadiyah 2 elementary school students, Pontianak. It is recommended that parents of students play an important role in the development of young women to maintain the fulfillment of good nutrition as well as provide assistance and convey information about menstruation.